Interspecific cytogenomic comparison reveals a potential chromosomal centromeric marker in Proceratophrys frog species - da Silva, Marcelo João [UNESP]; Destro, Raquel Fogarin [UNESP]; Gazoni, Thiago [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (My University, 2024)
Among the repetitive elements, satellite DNA (SatDNA) emerges as extensive arrays of highly similar tandemly repeated units, spanning megabases in length. Given that the satDNA PboSat01-176, previously characterized in P. boiei, prompted our interest for having a high abundance in P. boiei and potential for centromeric satellite, here, we employed various approaches, including low coverage genome sequencing, followed by computational analysis and chromosomal localization techniques in four Proceratophrys species and, investigating the genomic presence and sharing, as well as its potential for chromosomal centromere marker in Proceratophrys frog species. Our findings demonstrate that PboSat01-176 exhibits high abundance across all four Proceratophrys species, displaying distinct characteristics that establish it as the predominant repetitive DNA element in these species. The satellite DNA is prominently clustered in the peri/centromeric region of the chromosomes, particularly in the heterochromatic regions. The widespread presence of PboSat01-176 in closely related Proceratophrys species reinforces the validity of the library hypothesis for repetitive sequences. Thus, this study highlighted the utility of the satDNA family PboSat01-176 as a reliable centromeric marker in Proceratophrys species, with potential to be applied in other species of anuran amphibians. The observed sharing and maintenance of this sequence within the genus suggest possibilities for future research, particularly through expanded sampling to elucidate parameters that underlie the library hypothesis and the evolutionary dynamics of satDNA sequences.
Keywords: Amphibia; Chromosome; Cytogenetics; Evolution; Repeatmasker